Model Test and Back Analysis of Shield Tunnel Load Distribution in Soft Clay - Haoshuang Niu; Xiaolin Weng; Chao Tian; Deng Wang (Advances in Materials Science and Engineering)
Combined with the soft clay layer of Foshan metro, a back-analysis method combining model test and numerical simulation is developed. First, the similitude criterion for the model used in this study was derived from similarity theory and elasticity mechanics equations. Artificial clay is prepared by mixing kaolin, bentonite, loess, and river sand in proportions of 4 : 2: 3 : 1. Gypsum, water, and borax are mixed in proportions of 1 : 0.7 : 0.015 to simulate the tunnel lining. The model tests were carried out based on four load modes: the combination of mode 1, vertical load distribution and horizontal load linear distribution, mode 2, vertical load distribution and horizontal load parabolic distribution, mode 3, vertical load parabolic distribution and horizontal load linear distribution, and mode 4, vertical and horizontal load parabolic distribution. Then, the calculation model corresponding to the four load modes is established using ABAQUS, and the measured data is back-analyzed as the known quantity. The specific load values obtained were 359 kPa, 380 kPa, 361 kPa, and 368 kPa by the load-internal force curve. The bending moment and axial force are calculated by substituting the back-analysis load values back into the model and comparing the results with the measured values; it was found that the internal forces under the back-calculation load still deviated by varying degrees. By using the comprehensive error function E to evaluate the advantages and disadvantages of the four distribution modes, the comprehensive errors are 4.3%, 1.7%, 6.5%, and 5.9%, respectively. That is, the error of load distribution of mode 2 (the combination of vertical load distribution and horizontal load parabolic distribution) is the lowest and is highly consistent with the measured value, which is the closest to the characteristics of the load pattern of the stratum.